Economic Problems In Indonesia And Efforts To Solve Them - Marhaendo Purno (PT. Publikasiku Academic Solution, 2023)
Economic problems are one of the problems that arise today in our beloved country. Thus causing a hampering of economic growth. Therefore, the role of the government is very large, where the government is given the widest authority to manage its own government, including economic development based on potential wealth. To carry out this task, the government must play an active role in economic development. The method used in this study is a Qualitative approach. and the type of research is Descriptive. That is to describe the present reality. The results of this study show that the problems faced by the State of Indonesia include: Low economic growth in Indonesia, poverty, unemployment, income gap, foreign debt, budget deficit, industrial incompetence, inability to manage human resources, lack of mastery of science and technology, corruption, food crisis and centralized development. Efforts to overcome economic problems in Indonesia are by means of traditional economic systems, centralized economic systems, market economic systems, mixed economic systems and the implementation of national economic recovery programs by the government.